Benefits and barriers perceived by pregnant women of different socioeconomic status of Lima by eating food of animal origen - Quintana Salinas, Margot Rosario (2016)
Introduction. Anemia in pregnant women is a public health problem in Peru. One strategy to prevent it is dietary diversity, including foods of animal origin (FAO), iron sources and other nutrients of high bioavailability. The benefits and perceived barriers to eat these foods may differ according to socioeconomic status. Objective. To compare the benefits and perceived barriers regarding eating food of animal origin (FAO) among pregnant women of different socioeconomic status. Design. Qualitative study, phenomenology design. Institution. A health establishment located in Carabayllo (low socioeconomic status: LSES) and another one in Magdalena del Mar (medium socioeconomic status: MSES). Sample. 20 pregnant women of each socioeconomic status, chosen by age, number of children, body weight. Interventions. In-depth interviews and focus groups after informed consent. Main outcome measures. Benefits and barriers of eating FAO during pregnancy: meats and derivatives, fish, dairy products and eggs. Results. We found more similar benefits than different ones among both groups of pregnant women. FAO had high nutritional value, were good for the baby and mother, prevented anemia, eggs and chicken were versatile and practical to prepare, fish and liver were more nutritious among meats. There were similar barriers: poor accessibility due to cost, distaste, infrequent consumption, poor safety and intense organoleptic characteristics (smell, taste). Confusion about nutritional value in LSES and little food preparation skills in MSES. Conclusions. Participating pregnant women of different socioeconomic status (medium and low) perceived more similarities than differences in benefits and barriers regarding eating FAO.